Intelligence Room Auto Light Switcher - Mohd Asri, Muhammad Muhsin; Roslan, Muhammad Alif (2016)
Nowadays, the manually operated street lights are not switch off even when there are no people in the room. Therefore, in this project, the Intelligence Room Auto Light Switcher is proposed. It is a simple yet powerful concept, which uses sensor as a switch. By using this system it will improve the conventional method. It automatically switches on the light when there are people in the room. Moreover, it is automatically switch off light whenever there are no people in the room. Therefore by using this system energy consumption is also reduced.